The major histocompatibility complex: a model for understanding graft-versus-host disease - Petersdorf, Effie W. (Blood, 2013)
Acute graft-versus-host disease (GVHD) afflicts as much as 80% of all patients who receive an unrelated donor hematopoietic cell transplant (HCT) for the treatment of blood disorders, even with optimal donor HLA matching and use of prophylactic immunosuppressive agents. Of patients who develop acute GVHD, many are at risk for chronic GVHD and bear the burden of considerable morbidity and lowered quality of life years after transplantation. The immunogenetic basis of GVHD has been the subject of intensive investigation, with the classic HLA genetic loci being the best-characterized determinants. Recent information on the major histocompatibility complex (MHC) region of chromosome 6 as an important source of untyped genetic variation has shed light on novel GVHD determinants. These data open new paradigms for understanding the genetic basis of GVHD.